2012
DOI: 10.1007/s00415-012-6510-x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin as treatment for focal dystonia: a systematic review of the pharmaco-therapeutic and pharmaco-economic value

Abstract: Focal dystonia is a common, invalidating neurologic condition characterized by involuntary, sustained muscle contractions causing twisting movements and abnormal postures in one body part. Currently, botulinum toxin is the treatment of first choice. We performed a systematic review towards the pharmaco-therapeutic and pharmaco-economic value of botulinum toxin as treatment for focal dystonia, which yielded the following results. Botulinum toxin is the most effective treatment for reducing dystonic symptoms mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
(133 reference statements)
1
42
0
2
Order By: Relevance
“…At the average age of 40 years, almost half of the patients quit working or retire early due to dystonia, and 10 years later, only 25% of patients are working compared to 62% of the general population (Zoons 2012). Moreover, health-related quality of life is significantly diminished, mainly attributable to depression and anxiety, with scores comparable to patients with multiple sclerosis, Parkinson's disease or stroke (Zoons 2012).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…At the average age of 40 years, almost half of the patients quit working or retire early due to dystonia, and 10 years later, only 25% of patients are working compared to 62% of the general population (Zoons 2012). Moreover, health-related quality of life is significantly diminished, mainly attributable to depression and anxiety, with scores comparable to patients with multiple sclerosis, Parkinson's disease or stroke (Zoons 2012).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Reviews of "oNT treatment for CD suggest that 70-90% of patients derive symptomatic beneit from "oNT with at least one injection [29][30][31]. In a meta-analysis (8 trials with 361 patients using Ona"oNT"; 5 trials with 319 patients using "bo"oNT"), it was shown that there was a statistically and clinically signiicant improvement on objective rating scales and subjective rating scales as well as for pain relief in subjective scales [7].…”
Section: Treatment Of Cervical Dystoniamentioning
confidence: 99%
“…The botulinum toxins continue to serve as the main therapy for most patients with focal and segmental dystonia (3941), including both isolated or combined dystonia syndromes. Several safe and effective formulations are available in different parts of the world.…”
Section: New Diagnostic and Treatment Strategies For Combined Dystonimentioning
confidence: 99%